Kontestasi Hadis dalam Tagar Potong Kuku (#PotongKuku) di Media TikTok - Rukmana, Fachruli Isra; MH, Syahidil Mubarik; Yuzar, Sri Kurniati (UIN Sultan Syarif Kasim Riau, 2024)
This study seeks to examine the critical role of falsification in the interpretation of the Prophet’s hadith through the hashtag #potongkuku on the TikTok platform, with particular attention to its recommendations, user engagement, and implications for religious authority within digital environments. The research addresses an emerging phenomenon in hadith studies amid the disruption era, wherein social media has become a predominant medium for the dissemination and study of hadith. Prior to the advent of digital technology, the study of the Prophet’s hadith was primarily conducted through face-to-face learning circles in mosques and Islamic boarding schools. Currently, this process has transitioned into an online domain that is more inclusive and accessible. A notable example is the #potongkuku hashtag, which features excerpts from sermons by Habib Rifky Alaydrus and functions as a conduit for propagating hadith-based values in virtual spaces. Employing a qualitative methodology, this study utilizes content analysis techniques applied to videos and user comments associated with the #potongkuku hashtag as primary data, supplemented by relevant scholarly literature as secondary data. The findings reveal that hashtags facilitate the organization and retrieval of da‘wah themes, broaden the dissemination of hadith, and promote public participation in religious discourse. Nevertheless, the study also identifies instances of content citing hadiths without credible sources, underscoring the necessity of tabayyun (verification) and scholarly validation in the consumption of digital religious content. In sum, the #potongkuku phenomenon exemplifies a positive transformation in hadith learning and highlights the role of social media as a novel arena for the authentication and dissemination of Islamic knowledge.Abstrak: Penelitian ini bertujuan menganalisis urgensi falsifikasi dalam memahami hadis Nabi melalui tagar #potongkuku di aplikasi TikTok, dengan menyoroti anjuran, respons pengguna, serta relevansinya bagi otoritas keagamaan di ruang digital. Kajian ini berangkat dari fenomena baru dalam studi hadis di era disrupsi, ketika media sosial menjadi medium utama penyebaran dan pembelajaran hadis. Sebelum kemajuan teknologi digital, masyarakat mempelajari hadis Nabi melalui majelis ilmu di masjid atau pesantren secara tatap muka. Kini, proses tersebut bertransformasi ke ranah daring yang lebih inklusif dan terbuka. Salah satu fenomena yang menonjol adalah tagar #potongkuku, yang berisi potongan ceramah Habib Rifky Alaydrus dan menjadi sarana penyebaran nilai-nilai hadis di ruang maya. Penelitian ini menggunakan metode kualitatif dengan teknik analisis konten terhadap video dan komentar pengguna dalam tagar #potongkuku sebagai data primer, sedangkan literatur ilmiah digunakan sebagai data sekunder. Hasil penelitian menunjukkan bahwa penggunaan tagar memudahkan pencarian dan pengelompokan tema dakwah, memperluas jangkauan penyebaran hadis, dan mendorong partisipasi publik dalam diskursus keagamaan. Namun, penelitian juga menemukan adanya konten yang mengutip hadis tanpa sumber valid, yang menegaskan pentingnya tabayyun dan verifikasi ilmiah dalam konsumsi dakwah digital. Secara keseluruhan, fenomena tagar #potongkuku mencerminkan transformasi positif dalam pembelajaran hadis dan menegaskan peran media sosial sebagai ruang baru bagi otentikasi serta diseminasi ilmu keislaman.